The Evidence-Based Approach to Adult-Onset Idiopathic Nephrotic Syndrome - Canetta, Pietro A. A.; Radhakrishnan, Jai (Frontiers in Pediatrics, 2015)
Adult-onset nephrotic syndrome differs from its pediatric counterpart in several important ways. Most importantly, nephrotic syndrome in adults is more etiologically heterogeneous compared to children, and thus treatment approaches rely heavily on the histologic diagnosis provided by renal biopsy. The evidence-based approach to treatment of adult nephrotic syndrome has been critically examined by the Kidney Disease Improving Global Outcomes (KDIGO) guidelines in glomerulonephritis, published in 2012. Here, we examine the strengths and limits of those guidelines and review recent work that expands the evidence-based approach.